High-Frequency Ultrasound in the Evaluation of Psoriatic Arthritis: A Clinical Study. (July 2015) - Lin, Zhiguo; Wang, Yu; Mei, Yifang; Zhao, Yanping; Zhang, Zhiyi
Abstract: Background: This study aimed to compare high-frequency ultrasound (HFU) findings in the fingers with psoriatic arthritis (PsA) and rheumatoid arthritis (RA) and to explore the potential use of HFU in the early diagnosis of PsA. Methods: Forty-four PsA patients with 123 fingers with symptoms, 39 RA patients with 122 fingers with symptoms and 20 healthy patients were recruited as controls. The ultrasound imaging manifestation and blood flow of fingers were recorded and compared. The results were analyzed by the χ 2 test. Results: Abnormal ultrasound findings in the fingers of RA and PsA patients were identified and compared. Among RA patients, 82 (67.21%) were diagnosed with joint effusion, 78 (63.93%) were synovial thickening and 59 (48.36%) were bone erosion, while no tenosynovitis, soft tissue inflammation or enthesitis was found. However, among the patients with PsA, 75 (60.97%) were diagnosed with joint effusion, 68 (55.28%) were synovial thickening, 71 (57.72%) were bone erosion, 71 (57.72%) were tenosynovitis, 44 (35.77%) were soft tissue inflammation and 39 (31.70%) were enthesitis. Conclusions: HFU proved valuable in detecting soft tissue inflammation and enthesitis in the fingers of PsA patients. HFU may be an easy, safe and effective examination in the early diagnosis of PsA and observation of pathological changes of PsA.